Pengaruh Promotion, Brand Awareness, dan Price Discount terhadap Purchase Decision Produk Raja Ngemil di E-Commerce TikTok - Nisha Fadila; Mochamad Malik Akbar Rohandi; Dedy Ansari Harahap (UNISBA Press, 2024)
Abstract. This research was conducted based on the phenomenon that occurred, namely that there was a decline in sales of Raja Ngemil products on E-commerce Tiktok in the Promotion, Brand Awareness and Price Discount variables. So this research aims to determine the influence of Promotion, Brand Awareness, and Price Discount on Purchase Decisions for Raja Ngemil products in Tiktok E-commerce, as well as analyzing how big the influence of Promotion, Brand Awareness, and Price Discount are on Raja Ngemil products in Tiktok E-commerce. This research is a type of descriptive and verification research with quantitative methods. The sampling technique used is nonprobability sampling, namely purposive sampling. The population in this study were consumers who had purchased Raja Ngemil products on Tiktok e-commerce at least once and obtained a sample of 180 people. Then the data collection technique in this research is by distributing questionnaires. The results of this research can be concluded that: Simultaneously, there is a positive and significant influence between the variables Promotion, Brand Awareness, and Price Discounts on Purchase Decisions for Raja Ngemil products on E-commerce Tiktok. Abstrak. Penelitian ini dilakukan berdasarkan fenomena yang terjadi bahwa terdapat penurunan pada penjualan Produk Raja Ngemil di E-commerce Tiktok pada variabel Promotion, Brand Awareness, dan Price Discount. Sehingga penelitian ini bertujuan untuk mengetahui pengaruh Promotion, Brand Awareness, dan Price Discount terhadap Purchase Decision pada produk Raja Ngemil di E-commerce Tiktok, serta menganalisis seberapa besar pengaruh Promotion, Brand Awareness, dan Price Discount pada produk Raja Ngemil di E-commerce Tiktok. Penelitian ini merupakan jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang telah melakukan pembelian produk Raja Ngemil di e-commerce Tiktok minimal 1 kali dan didapatkan sampel sebanyak 180 orang. Lalu teknik pengumpulan data pada penelitian ini adalah dengan cara penyebaran kuesioner. Hasil dari penelitian ini dapat disimpulkan bahwa: Secara simultan, terdapat pengaruh positif dan signifikan antara variabel Promotion, Brand Awareness, dan Price Discount terhadap Purchase Decision pada produk Raja Ngemil di E-commerce Tiktok.